Consumer Brand Preference in Buying Car in Nepal - Rai, Bharat (KMC Research Journal, 2019)
The main objective this study is to identify the factors affecting the consumer brand preference in the choice of car in Kathmandu, Nepal. The study examines how the price perception, appearance perception and brand personality affect in the consumer brand preference in the buying of car in Nepalese market. The study focuses on how the consumer preferred to select the car and which factor has the more prominent role for brand preference and selection of car. Primary data has been used in the study. The structured questionnaire has been used for collection of primary data. Convenient sampling technique has been used to collect information from the respondents and 265 respondents have been taken from customers buying car in Kathmandu. Descriptive statistical analysis, correlation analysis and path analysis have been used to diagnose data collected to draw valid conclusions using SPSS AMOS 21. Price perception, appearance perception and brand personality are taken as independent variables to explore the degree of relationship with consumer behavior and to explore the impact of these variables on consumer behavior while making decision to purchase a car. Correlation showed that all independent variables have significant relationship with dependent variable. The path analysis showed that there is a significant impact of appearance perception and brand personality on consumer behavior in buying of car but price perception has no significant impact on consumer behavior in buying of car in Nepalese market.